Peranan Manajemen Perubahan dalam Perkembangan Organisasi : Studi Kasus pada Organisasi Himpunan Jurusan Manajemen Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara - Raudah Azzahra Manurung; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
Change is an unavoidable process in organizations. Organizational change is the process of moving from a current state to a future state in order to improve the organization. Organizations are constantly changing to anticipate and meet future challenges. Organizational change can occur from outside or from within the organization itself, both in the form of planned and structural changes that need to be managed properly. The method used in the application of this research is research based on qualitative. The type of research used is a literature study. It can be concluded that organizational management is needed to support the change process so that the organization can improve its development. The development of an organization has a great impact on the success or failure of the organization. Organizational change is not always popular because we are reluctant to make all the changes. The existence of organizational change can pose a risk of failure for the organization and requires proper management so that the organization can progress.